MINYAK NILAM (Patchouli alcohol) SEBAGAI ANTIOKSIDAN DENGAN METODE DPPH (1,1-difenil-2-pikrilhidrazil) - Agus Suprijono; Yoel Gunawan; Ariani Hesti Wulan (Universitas Wahid Hasyim Semarang, 2015)
ABSTRACTAlong with the rapid flow of information and globalization, led to the lifestyle of modern society is also becoming more and more advanced. But this was not accompanied by increased quality of public health. Lifestyle such as this may result in exposure to free radicals degna. Antioxidants are compounds that can inhibit the oxidation of free radicals, so it will form a more stable compound. Oil Patchouli (Patchouli oil) contains patchouli alcohol which have antioxidant activity. The rate is determined by the quality of patchouli oil patchouli alcohol content therein. The purpose of this research is to show the antioxidant activity of patchouli oil and standard determine differences in activity with BHT, as well as to determine the effective concentration expressed in EC50 values by using DPPH method. The examination was conducted by using the test solution at a concentration of 5%, 10%, 15%, 20% and 25%. The process to obtain the patchouli oil is done by means of steam distillation of the dried herb patchouli. Identification test to determine the quality of the oil produced by TLC test and also qualitative test to determine the antioxidant activity. From the research it can be seen that the average value of EC50 for patchouli oil sample is equal to 19.95%, while 11.93% of standard BHT. Based on these results, concluded that the antioxidant activity in patchouli oil, and there are significant differences in antioxidant activity between standard patchouli oil with BHT.Keywords: patchouli oil, patchouli alcohol, anti-oxidant, DPPH.